Determination of trace amounts of water in propylene carbonate using the proton isoconcentration technique - Rashid, M.; Karim, O.; Hussain, Mohd Azlan (The Analyst, 1987)
Direct potentiometry of the system propylene carbonate (PC) - 0-1 m/m water -10 -3 M perchloric acid as a solution in glacial acetic acid, using glass pH and silver - silver chloride reference electrodes with a filling solution of saturated tetraethylammonium chloride in PC, shows a large systematic change in potential with variations in water concentration. This technique allows the fast and accurate determination of residual water in binary propylene carbonate mixtures.